Reassessment of the Four Yield-related Genes Gn1a, DEP1, GS3, and IPA1 in Rice Using a CRISPR/Cas9 System - Li, Meiru; Li, Xiaoxia; Zhou, Zejiao; Wu, Pingzhi; Fang, Maichun; Pan, Xiaoping; Lin, Qiupeng; Luo, Wanbin; Wu, Guojiang; Li, Hongqing (Frontiers in Plant Science, 2016)
Clustered Regularly Interspaced Short Palindromic Repeats (CRISPR)-associated (Cas) systems have been successfully used as efficient tools for genome editing in a variety of species. We used the CRISPR/Cas9 system to mutate the Gn1a (Os01g0197700), DEP1 (Os09g0441900), GS3 (Os03g0407400) and IPA1 (Os08g0509600) genes of rice cultivar Zhonghua 11, genes which have been reported to function as regulators of grain number, panicle architecture, grain size and plant architecture, respectively. Analysis of the phenotypes and frequencies of edited genes in the first generation of transformed plants (T0) showed that the CRISPR/Cas9 system was highly efficient in inducing targeted gene editing, with the desired genes being edited in 42.5% (Gn1a), 67.5% (DEP1), 57.5% (GS3) and 27.5% (IPA1) of the transformed plants. The T2 generation of the gn1a, dep1, and gs3 mutants featured enhanced grain number，dense erect panicles and larger grain size, respectively. Furthermore, semi-dwarf, and grain with long awn, phenotypes were observed in dep1 and gs3 mutants, respectively. The ipa1 mutants showed two contrasting phenotypes, having either fewer tillers or more tillers, depending on the changes induced in the OsmiR156 target region. In addition, we found that mutants with deletions occurred more frequently than previous reports had indicated and that off-targeting had taken place in highly similar target sequences. These results proved that multiple regulators of important traits can be modified in a single cultivar by CRISPR/Cas9, and thus facilitate the dissection of complex gene regulatory networks in the same genomic background and the stacking of important traits in cultivated varieties.